Comparison of WHO Growth Standards with 2019 Indian Synthetic Growth Charts in Children under Five Years of Age: A Cross-sectional Study from Rural Area of Karnataka, India - Shalini Yadhav; AS Jagadish; R Premalatha; B Ravichander (Indian Journal of Neonatal Medicine and Research)
Introduction: Growth monitoring is a crucial screening tool that aids in the early diagnosis of various nutritional, chronic systemic and endocrine diseases. The choice of reference charts used to measure different measures of nutritional status can significantly impact the accuracy of these indicators, which, in turn, affects the assessment of government initiatives aimed at improving healthcare outcomes. Aim: To compare the World Health Organisation (WHO) and 2019 Indian synthetic growth charts in children under five years of age from rural area of Karnataka, and to study the nutritional status of predominantly breastfed infants less than six months of age using the two charts. Materials and Methods: This cross-sectional study was conducted at MVJ Medical College and Research Hospital, Bengaluru, Karnataka, India, from July 2022 to July 2024. The study included a sample size of 1,252 children between the ages of 0-60 months who presented to the Outpatient Department (OPD) or attended Anganwadi centres. Demographic details such as name, age, sex, birth weight, and gestation at birth were collected using a predesigned proforma. Anthropometric parameters were measured. The measured variables (height, weight, and Body Mass Index (BMI)) were plotted on both the WHO charts and the 2019 Indian synthetic charts and classified accordingly. A paired t-test was used to compare the mean values between variables, while McNemar’s test was used to compare the proportions for the variables. Results: Of the 1,252 children included in the study, 764 (61%) were males and 488 (39%) were females. Mean birth weight of the subjects was 2.85±0.44 kg. On WHO charts, the mean Z scores for height, weight and BMI was -1.28±1.54, -1.18±1.12, and -0.58±1.32 whereas on Synthetic charts, it was -0.61±1.36, -0.58±1.34, and 0.36±1.70, respectively. The analysis revealed a significant difference in Z scores when measured by WHO charts and synthetic charts (p-value<0.001). Conclusion: The use of synthetic growth charts may be more suitable for Indian children when compared to the WHO charts, as suggested by statistically significant difference in Z scores of measured variables.